A STAGGERED SCHEME WITH ADAPTIVE TIME STEP CONTROL FOR FLUID-STRUCTURE INTERACTION - Miras, Thomas; Rochinha, Fernando A.; Coutinho, Alvaro L.G.A. (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The coupling between a rigid body and an incompressible fluid is investigated. Within the framework of ALE, we use a residual-based variational multiscale (RBVMS) formulation to solve the incompressible Navier Stokes equations. Mesh updating is accomplished by a parallel edge-based solution of a non-homogeneous scalar diffusion problem in each spatial coordinate. This work is in the continuation of previous results presented in Miras et al. (2015). We use here a staggered type of coupling with a prediction/correction approach for the forces applied on the rigid body. A time stepping by a Proportional-Integral-Derivative controller based on the CFL number is also presented. The coupling approach is tested on different cases coming from the literature and in the area of Vortex Induced Vibrations (VIV), allowing to evaluate the performance of the method in term of accuracy and robustness. We give particular attention to the parameters used to compute the force/moment prediction.